Teacher agency in the times of crisis: a situational analysis of school environment after the 2022 Russian invasion in Ukraine - Szczepaniak-Kozak, Anna; Wąsikiewicz-Firlej, Emilia (Frontiers in Psychology, 2024)
From February to May 2022, the war in Ukraine prompted Poland to accommodate 3.37 million refugees from conflict zones, in addition to 850 thousand Ukrainian economic migrants already residing in the country. A substantial proportion of these refugees, primarily mothers with children, swiftly integrated into the Polish educational system, with some children commencing schooling within a week of their arrival. This influx significantly diversified the then predominantly monolingual landscape of Polish schools. Given the uniqueness of this situation and the fact that Poland has historically remained mono-national and monolingual for decades, Polish teachers suffered from a lack of preparedness, resources and expertise to effectively navigate their teaching practices in multilingual classes. To understand the specificity of this situation, taking especially into account the perspective of educators, we have designed a qualitative study drawing on focus group and individual interview reports. We were particularly interested in determining how teachers' agency was activated in times of crisis. The findings reveal how the newly-emerging linguistic and cultural heterogeneity is perceived by teachers, how it is manifested in school and home environments, and the extent to which possibilities for synergies exist between the two. The findings also highlight the fact that, despite teachers' inexperience and unpreparedness for the new educational context, they instantly responded to the challenges that emerged. This can be exemplified by teachers' collaboration in material design as well as the willingness to participate in courses sensitizing to migrant students' needs (e.g., linguistic, educational, or emotional ones).